Health Deteminants Of Home Physical Condition Factors Incidence Of Pulmonary Tb In The Nganjuk Community Helath Center Working Area 2020 - Sherly Novalia Rahmawati; Setyo Budi Susanto (Universitas STRADA Indonesia, 2019)
Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium tuberculosis). A house that does not meet health requirements is a risk factor for pulmonary tuberculosis. This study aims to analyze factors in the physical condition of houses on the incidence of pulmonary TB in the Nganjuk health center working area in 2020. This research is a type of analytical survey research with a case control study design. The population in this study was pulmonary TB sufferers and non-pulmonary TB sufferers, totaling 82 people. The sampling technique uses total sampling. Data analysis uses logistic regression analysis. The results of the research show that the physical condition of the house that influences the incidence of TB in the Nganjuk Community Health Center working area is ventilation with a significant value of 0.002 with an R odd = 1.424.